Forensic Odontology: A Tool in Criminal Investigation - Singh, O. Gambhir (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
The knowledge of dentistry is utilized in various criminal investigations. Forensic Odontologists are involved in assisting investigative agencies to identify recovered human remains in addition to the identification of whole or fragmented bodies. Forensic dentists have also been known to use their investigative techniques to identify burn victims by using the victim’s previous dental records. Various useful information like age, sex, race, occupation, personal habits, disease condition, etc. of a person. This is especially useful in the identification of unknown mutilated or highly decomposed unknown bodies. The main aim of the present chapter is to discuss its various applications in criminal investigations.